ANALISIS WACANA KRITIS PADA STAND UP COMEDY INDONESIA - Idha Nurhamidah; Pahriyono Pahriyono; Sumarlam Sumarlam (Universitas Sebelas Maret, 2020)
This study aims to demystify the stereotypes of Eastern Indonesian citizens. Specifically, the problem of this study is formulated as: (1) What rhetorical strategy and text structure are used in developing themes?, (2) What social cognition can be identified through audience response to the stereotypes of Eastern Indonesian citizens? (3) What social context can be built in response to the stereotype of Eastern Indonesian citizens? The object of study in the form of transactional oral text delivered by the comic Abdur Arsyad at Show 8, SUCI season 4, with the theme of Women, was taken randomly and analyzed with the critical discourse study approach by Teun A. Van Dijk, free-of-charge skills, and methods extra lingual equivalent. The findings of this study indicate that Abdur uses epideictic rhetoric in the form of a single unit in a text structure (joke map), consisting of 13 sub-goals, each containing 3 phases, namely: premise, set-up, and punchline. Meanwhile, cognition in the form of 10 allusions and stereotypes of the rigors of Eastern Indonesian citizens proved to be within the scope of audience knowledge through applause. Furthermore, the social context - a stereotype of Eastern Indonesian citizens was built to explain the cultural background and comic efforts to reduce the stereotype. Thus this study has a significant contribution to the addition of linguistic treasures related to Stand Up Comedy linguistic activities.